Climate Change and Public Health Policy. Issue 1 (2017) - Smith, Jason A.; Vargo, Jason; Hoverter, Sara Pollock
Abstract : Climate change poses real and immediate impacts to the public health of populations around the globe. Adverse impacts are expected to continue throughout the century. Emphasizing co-benefits of climate action for health, combining adaptation and mitigation efforts, and increasing interagency coordination can effectively address both public health and climate change challenges.